Purinergic Signaling in Liver Pathophysiology - Jain, Shanu; Jacobson, Kenneth A. (Frontiers in Endocrinology, 2021)
Extracellular nucleosides and nucleotides activate a group of G protein-coupled receptors (GPCRs) known as purinergic receptors, comprising adenosine and P2Y receptors. Furthermore, purinergic P2X ion channels are activated by ATP. These receptors are expressed in liver resident cells and play a critical role in maintaining liver function. In the normal physiology, these receptors regulate hepatic metabolic processes such as insulin responsiveness, glycogen and lipid metabolism, and bile secretion. In disease states, ATP and other nucleotides serve as danger signals and modulate purinergic responses in the cells. Recent studies have demonstrated that purinergic receptors play a significant role in the development of metabolic syndrome associated non-alcoholic fatty liver disease (NAFLD), non-alcoholic steatohepatitis (NASH), fibrosis, hepatocellular carcinoma (HCC) and liver inflammation. In this concise review, we dissect the role of purinergic signaling in different liver resident cells involved in maintaining healthy liver function and in the development of the above-mentioned liver pathologies. Moreover, we discuss potential therapeutic strategies for liver diseases by targeting adenosine, P2Y and P2X receptors.